2015
DOI: 10.1007/s11999-015-4380-0
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Soft Tissue Repair After Primary THA is Durable at Mid-term Followup: A Prospective MRI Study

Abstract: Background The enhanced posterior soft tissue repair has reduced the frequency of dislocation after primary THA performed through the posterolateral approach. However, the long-term integrity of the repair is unknown and could influence surgeon choice regarding surgical technique and THA approach. Questions/Purposes We asked: (1) What is the durability of the enhanced posterior soft tissue repair at a minimum of 49 months using MRI to evaluate soft tissue to bone integrity? (2) How does the appearance of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 20 publications
2
31
0
3
Order By: Relevance
“…Longitudinal analysis of this repair technique using MRI has shown that the piriformis and conjoined tendons form hypointense scar that aligns along the long axis of the original tendon, preventing clinical instability despite early failure of the repair. 83,84 Recurrent hemarthrosis may occur in patients following arthroplasty due to hyperemic, friable synovium and/or areas of synovial impingement. On MRI, hemarthrosis appears as a complex synovitis with bulky intermediate signal intensity deposits.…”
Section: Arthroplasty Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal analysis of this repair technique using MRI has shown that the piriformis and conjoined tendons form hypointense scar that aligns along the long axis of the original tendon, preventing clinical instability despite early failure of the repair. 83,84 Recurrent hemarthrosis may occur in patients following arthroplasty due to hyperemic, friable synovium and/or areas of synovial impingement. On MRI, hemarthrosis appears as a complex synovitis with bulky intermediate signal intensity deposits.…”
Section: Arthroplasty Complicationsmentioning
confidence: 99%
“…In a classic posterior surgical approach, the short external rotators tendons are released and subsequently repaired. Longitudinal analysis of this repair technique using MRI has shown that the piriformis and conjoined tendons form hypointense scar that aligns along the long axis of the original tendon, preventing clinical instability despite early failure of the repair (83,84)…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate this risk, posterior soft-tissue reconstruction is often performed at the time of surgery to enhance hip joint stability [23]. As such, it is imperative to assess the integrity of the posterior joint capsule and short external rotator muscles.…”
Section: Imaging Of Arthroplasty-associated Complicationsmentioning
confidence: 99%
“…Posterior capsular dehiscence can be appreciated at MRI by a lack of continuity of the posterior pseudocapsule and short external rotators with the greater trochanter, often showing a fluid-filled gap interposed between the two, with or without associated anterior pseudocapsular thickening and hyperintensity. Longitudinal MRI studies indicate that the repairs fail early but that the retracted tendons form scar-in-continuity that aligns with the tendon long axis and prevents instability in most cases [23]. …”
Section: Imaging Of Arthroplasty-associated Complicationsmentioning
confidence: 99%
“…tendons are in continuity directly, or through scar, with the greater trochanter in 96% of patients [12]. The soft tissue restraint conferred by this technique is effective at reducing dislocation incidence but does not eliminate it [5,10].…”
Section: Introductionmentioning
confidence: 99%